“Why Don’t Consumers Care About CSR?”: A Qualitative Study Exploring the Role of CSR in Consumption Decisions - Öberseder, Magdalena; Schlegelmilch, Bodo B.; Gruber, Verena (2011)
There is an unresolved paradox concerning the role of corporate social responsibility (CSR) in consumer behavior. On the one hand, consumers demand more and more CSR information from corporations. On the other hand, research indicates a considerable gap between consumers’ apparent interest in CSR and the limited role of CSR in purchase behavior. This article attempts to shed light on this paradox by drawing on qualitative data from in-depth interviews. The findings show that the evaluation of CSR initiatives is a complex and hierarchically structured process, during which consumers distinguish between core, central, and peripheral factors. This article describes these factors in detail and explains the complexity of consumers’ assessment of CSR. These insights then serve as a basis for discussing the theoretical and managerial implications of the research findings. To this end, the article contributes to a better understanding of the role of CSR in consumption decisions.
Keywords: Qualitative Research; Purchase Intention; Consumer behavior; Corporate Social Responsibility